2023
DOI: 10.3390/jcm12082801
|View full text |Cite
|
Sign up to set email alerts
|

Dental Manifestations and Celiac Disease—An Overview

Abstract: This review summarizes recent investigations on dental manifestations in celiac disease. Particular attention is paid to delayed dental eruption and maturity, dental enamel defects, molar incisor hypomineralization, dental caries, dental plaque, and periodontitis. Most studies confirmed a higher frequency of delayed dental eruption and maturation in children and dental enamel defects in children and adults with celiac disease compared to healthy individuals. The malabsorption of various micronutrients, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A recent paper by Ahmed et al [ 21 ] on 118 CD patients and 40 controls showed that DED was present in 66.9% of adult patients with CD (age range 20–37.23 vs. 21.3–36.8). The correlation between CD and DEDs could involve factors beyond nutritional deficiencies, including the timing of amelogenesis interruption and autoimmune reactions against amelogenins and ameloblastin, which guide enamel mineralization [ 54 ]. Sera from CD patients can recognize amelogenins, a prominent component in the enamel matrix; this was further supported by the discovery of high IgG reactivity against gliadin peptides and enamel matrix protein extract in patients with untreated CD, indicating a pathological role for antibodies to gliadin in DEDs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Ahmed et al [ 21 ] on 118 CD patients and 40 controls showed that DED was present in 66.9% of adult patients with CD (age range 20–37.23 vs. 21.3–36.8). The correlation between CD and DEDs could involve factors beyond nutritional deficiencies, including the timing of amelogenesis interruption and autoimmune reactions against amelogenins and ameloblastin, which guide enamel mineralization [ 54 ]. Sera from CD patients can recognize amelogenins, a prominent component in the enamel matrix; this was further supported by the discovery of high IgG reactivity against gliadin peptides and enamel matrix protein extract in patients with untreated CD, indicating a pathological role for antibodies to gliadin in DEDs.…”
Section: Discussionmentioning
confidence: 99%
“…Several dental manifestations have been described in CeD in particular, such as delayed dental eruption and maturity in children, dental enamel defects (DEDs), dental caries, dental plaque, and periodontitis in children and adults [ 8 ] ( Figure 2 ; Table 1 ). A case–control study from Saudi Arabia evaluated the presence of DEDs in 104 children with CeD and 104 non-CeD children [ 9 ].…”
Section: Oral Cavity Nose and Earsmentioning
confidence: 99%
“…Early diagnostics for CeD and a strict GFD may help prevent these complaints. Recent investigations supplemented older contradictory studies on the association between CeD and dental caries, dental plaque, and periodontitis; however, clear conclusions could not be reached [ 8 ]. All in all, the link between CeD and DED has been proved.…”
Section: Oral Cavity Nose and Earsmentioning
confidence: 99%
“…The oral cavity is intricately connected to systemic health, and changes in oral tissues can reflect underlying systemic conditions [ 64 ]. Recognizing the oral manifestations of CD, particularly enamel defects, emphasizes the role of dentists as integral contributors to the comprehensive healthcare team [ 65 ].…”
Section: Introductionmentioning
confidence: 99%